RANCANG BANGUN SISTEM PENGENDALI PH OTOMATIS PADA KOLAM BUDIDAYA IKAN NILA - Mege, Christio Revano; Louhenapessy, Stevy Canny; Khoirunisa, Vera; Putra, Septia Eka Marsha; Simanullang, Astuti BP (Jurnal Media Elektro, 2024)
Water quality is one of the important factors to increase the success of aquaculture production besides disease factors and fish seed quality. Water quality in auaculture ponds greatly affects the growth, survival, and production of tilapia. Several factors that affect water quality are the acidity level (pH). The maximum pH value ranges from 6.5 to 8.5. This study aims to design an automatic water pH control system in tilapia ponds. The water quality control system in fish ponds is often done manually so it is less efficient. The system is designed by combining a pH sensor pump, and solenoid valves using ESP32 microcontroller. When the pH sensor detects a pH value of less than 6.5 or more than 8.5, the system will automatically change the water. The test results in the pond showed that the system was able to respond with the respective rise time and settling time values, namely 1240s and 1380s. Based on these results, it can be concluded that the pH control system that was built can function according to the design.